Electrochemical synthesis of 1, 2, 4-oxadiazoles from amidoximes through dehydrogenative cyclization. Issue 48 (2nd December 2021) - Jiang, Chan; Li, Mingfang; Xu, Leitao; Yi, Yangjie; Ye, Jiao; Hu, Aixi
Abstract : The iminoxy radical generated through anodic oxidation from amidoximes undergoes 1, 5-HAT and intramolecular cyclization to obtain 1, 2, 4-oxadiazoles in good to high yields. Abstract : A convenient and efficient method for the generation of the iminoxy radical through anodic oxidation was developed for the synthesis of 3, 5-disubstituted 1, 2, 4-oxadiazoles from N -benzyl amidoximes. The transformation proceeds through 1.5-Hydrogen Atom Transfer (1, 5-HAT) and intramolecular cyclization. The process features simple operation, mild conditions, broad substrate scope and high functional group compatibility, and provides a facile and practical way for the preparation of 1, 2, 4-oxadiazoles.